(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the article the indexes of the average monthly charged extra salary in Republic of Poland for 2012–2014 are considered. Grouping of types of economic activity after two authorial methodologies: 1) depending on the size of monthly profits; 2) depending on the got rating position, is conducted. Data about education are analysed. The got results with analogical in Ukraine are compared. The level of remuneration of labour of Poland appeared higher, than Ukrainians. The most high-paying sphere in a nearby country is mining and quarrying, the least pay – accommodation and catering. It is indicated on expediency of realization of analogical researches on all other toneighbours of Ukraine: Russian Federation, Republic of Belarus, Slovak Republic, Hungary, Romania and Republic of Moldova.